CLINICAL CHARACTERISTICS AND RELATIONSHIP WITH KRAS, BRAF GENE MUTATIONS IN COLORECTAL CANCER PATIENTS - Hữu Đức, Hồ; Văn Hưng, Nguyễn (Journal of Health and Aging, 2025)
Colorectal cancer is one of the most common malignancies with high incidence and mortality rates. KRAS and BRAF mutations play a crucial role in its pathogenesis and prognosis, but their association with clinical characteristics in Vietnam requires further investigation. To investigate the prevalence of KRAS and BRAF mutations in colorectal cancer patients and analyze their relationship with clinical, epidemiological, and disease-stage features. A retrospective descriptive study was conducted on 92 colorectal cancer patients diagnosed and treated at Thong Nhat Hospital from February 2020 to December 2024. Data included demographic characteristics, clinical symptoms, tumor location, disease stage, and genetic mutation test results. The median age of patients was 66, with a male/female ratio of 2.1. Common symptoms included abdominal pain (71.7%) and bloody stools (38%). The mutation rates were 35.9% for KRAS (predominantly G12D and G12V), 6.5% for BRAF, and no NRAS mutations were detected. KRAS and BRAF mutations showed no significant association with age, gender, clinical symptoms, or disease stage (p>0.05), but were linked to peripheral lymphadenopathy (p=0.035). KRAS and BRAF mutations are relatively common in colorectal cancer patients but are not strongly associated with clinical features or disease stage. Genetic testing remains essential for personalized diagnosis and treatment.
Keywords: Colorectal cancer; KRAS mutation; BRAF mutation; clinical features; disease stage